Influence of phenolic acids on growth and inactivation of Oenococcus oeni and Lactobacillus hilgardii - Campos, F.M. (2011)
Aims: To determine the effect of several wine-associated, phenolic acids on the growth and viability of strains of Oenococcus oeni and Lactobacillus hilgardii. Methods and Results: Growth was monitored in ethanol-containing medium supplemented with varying concentrations of hydroxybenzoic acids (p-hydroxybenzoic, protocatechuic, gallic, vanillic and syringic acids) and hydroxycinnamic acids (p-coumaric, caffeic and ferulic acids). Progressive inactivation was monitored in ethanolcontaining phosphate buffer supplemented in a similar manner to the growth experiments. Hydroxycinnamic acids proved to be more inhibitory to the growth of O. oeni than hydroxybenzoic acids. On the other hand, some acids showed a beneficial effect on growth of Lact. hilgardii. p-Coumaric acid showed the strongest inhibitory effect on growth and survival of both bacteria. Conclusions: Most phenolic acids had a negative effect on growth of O. oeni, for Lact. hilgardii this effect was only noted for p-coumaric acid. Generally, O. oeni was more sensitive to phenolic acid inactivation than Lact. hilgardii. Significance and Impact of the Study: Eight wine-derived, phenolic acids were compared for their effects on wine lactic acid bacteria. Results indicate that phenolic acids have the capacity to influence growth and survival parameters. The differences found between phenolic compounds could be related to their different chemical structures.